Analisis Pengaruh Compressor Washing terhadap Efisiensi Thermal pada Turbin Gas PLTGU Blok 3.3 UP Muara Tawar dengan Pendekatan Sankey Diagram - Adam Wirya; Muhammad Ridwan (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
Gas turbines are one of the primary technologies in power generation due to their ability to produce energy quickly and efficiently. However, the performance of gas turbines can decline over time due to fouling on the compressor, which negatively impacts the thermal efficiency of the system. One common maintenance method to address this issue is compressor washing. This study aims to analyze the impact of compressor washing on the thermal efficiency of gas turbines at PLTGU UP Muara Tawar Block 3.3 and to identify the influencing factors, using the Sankey diagram approach. The study uses both primary and secondary data collected between March and August 2024. The results show a slight improvement in thermal efficiency after compressor washing, from a range of 12.319%–13.215% to 12.295%–12.811%. The Sankey diagram reveals an increase in net output and a reduction in compressor work after cleaning. The main factors affecting thermal efficiency include compressor fouling, ambient temperature variation, and the non-operational status of the HRSG unit during the observation period. These findings confirm that compressor washing contributes to restoring gas turbine performance and enhancing overall system efficiency. Keywords: Gas Turbine, Thermal Efficiency, Compressor Washing, Sankey Diagram